Sistem Monitoring Peternakan Ayam Broiler Berbasis Internet of Things (IoT) - Ari Ajibekti Masriwilaga; Tubagus Abdul Jabar Malik Al-hadi; Agus Subagja; Sopian Septiana (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
In this study, the author made a monitoring system for dangerous gas levels, temperature and humidity in the chicken coop. This system can inform air quality in the form of ammonia gas, methane gas, temperature and humidity contained in the chicken coop and provide readings of gas data that are considered dangerous, unstable temperature and humidity to workers in the chicken coop and can be viewed on a platform basis. The system generally consists of two sensors, namely the DHT11 sensor to detect temperature and humidity in the chicken coop, and the MQ135 sensor to detect ammonia gas levels in the chicken coop, and connect to the internet network through the ESP8266 module with the Arduino Mega 2560 microcontroller which aims to upload data sensors to the Firebase web and displayed in graphical form as a means of information on the chicken coop. The test is carried out in three stages, namely connectivity, functionality, and delay. The connectivity test proves that ESP8266 can be connected to Access Points and internet networks, functionality tests prove that sensors can read gas, temperature and humidity and retrieve data. And lastly is testing delay, which is counting the length of the process from the beginning of sensor reading to data up to Firebase's Internet of Things (IoT) -based web. From the results of calculations that have been done in testing, it was found that the time needed for one shipment takes as much as 5-19 seconds. Of course, this time can change because there are aspects that can inhibit internet connection, the number of devices connected to an internet network, but the purpose of this research has been completed with what was expected. Keywords : Hazardous Gas, Temperature and Humidity, Gas Sensors and Temperature and Humidity Sensors, Firebase.